Diagnostic value of computed tomography in the patients of abdominal tuberculosis - Salooja, B. S.; Mukhi, Sadhan (International Journal of Research in Medical Sciences, 2016)
Background: Abdominal tuberculosis (ATB) is a rare form of extra-pulmonary tuberculosis which is clinically challenging. It remains difficult to diagnose due to the non-specific presentation, variable anatomical location and lack of sensitive diagnostic tools. To evaluate the diagnostic value of computed tomography (CT) in the patients of abdominal tuberculosis. Methods: This was a retrospective diagnostic study design. The study was conducted among adults aged>18 years of either gender with clinical suspected ATB. The detailed demographic and clinical history was noted on pre-designed proforma. After obtaining the history, the patient was subjected to general physical and systematic examinations. The patients were then subjected to radiological evaluation that included chest X-ray, X-ray of abdomen and CT. Results: A total of 55 clinically suspected adult cases of abdominal tuberculosis were enrolled in the study. 45 (81.8%) were found to be abdominal tuberculosis on final diagnosis. The abdominal tuberculosis was found to be higher in the age groups 21-40 years (64.4%).The abdominal tuberculosis was observed to be higher among female patients (62.2%) than males (37.8%). CT findings showed that the bowel wall thickening & narrowing and dilatation was found in 64.4% patients. Conclusions: ATB is still a diagnosis to consider in individuals presenting with abdominal symptoms in the developing world, particularly in patients from ethnic minorities. Diagnosis can be challenging and requires a multidisciplinary approach with involvement from Radiology, Microbiology, Gastroenterology, Surgery, Infectious Diseases and Respiratory teams.